PRESERVATION OF YOUTH OATH VALUES THROUGH TEACHING HISTORY AS A MEANS OF REALIZING AN ATTITUDE OF NATIONALISM (CASE STUDY IN BANYUWANGI CITY HIGH SCHOOL) - Hoirus Sholeh (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2018)
This research is to find out the extent to which the values ​​of youth oath become an expression of nationalism through the teaching of history. The method used is a qualitative case study method in Banyuwangi City High School. The respondents were three teachers and several students who were taken as snowboll samples. The results showed that under various conditions, an erosion of national values ​​was felt that had been pioneered since 28 October 1982. The moral crisis engulfed the young generation so that the sense of patriotism and nationalism faded. The application of a sense of nationalism can be restored through learning history with the application of everyday life. Applications for increasing nationalism can utilize the school curriculum..